Identification and Quantification of Nitrogen in a Reservoir, Jiaodong Peninsula, China. (1st April 2017) - Zheng, Meng; Sheng, Yanqing; Sun, Ruichuan; Tian, Chongguo; Zhang, Haibo; Ning, Jicai; Sun, Qiyao; Li, Zhaoran; Bottrell, Simon H.; Mortimer, Robert J. G.
Abstract : Identification of nitrogen (N) sources is important in water quality control and management. Nitrogen pollution can lead to eutrophication of waterbodies and high concentrations of nitrate in drinking water can pose potential health problems. The 15 N isotope and nitrogen fluxes budget approach is useful for determining the source of NO3 ‐ to surface waters. In this study, mass balance and 15 N isotope approaches and nitrogen flux budgets were applied to identify total nitrogen (TN) sources and nitrogen transformation processes in the Menlou Reservoir (MR), Jiaodong Peninsula, China. The different fractions of nitrogen and their 15 N isotope signatures were analyzed in the reservoir water, river water, groundwater, soil, and atmospheric precipitation. The results indicate that surface runoff pollution (e.g., fertilizer and animal manure) is the main source of NO3 ‐ in MR. High concentrations of TN in MR are caused by low nitrogen self‐purification (denitrification) rate, low sediment adsorption capacity, and the influx of NO3 ‐ rich groundwater.